Factors associated with less-than-full-time working in medical practice: results of surveys of five cohorts of UK doctors, 10 years after graduation - Lachish, S; Svirko, E; Goldacre, M; Lambert, T (BioMed Central, 2016)
Background: The greater participation of women in medicine in recent years, and recent trends showing that doctors of both sexes work fewer hours than in the past, present challenges for medical workforce planning. In this study, we provide a detailed analysis of the characteristics of doctors who choose to work less-than-full-time (LTFT). We aimed to determine the influence of these characteristics on the probability of working LTFT. Methods: We used data on working patterns obtained from long-term surveys of 10,866 UK-trained doctors. We analysed working patterns at 10 years post-graduation for doctors of five graduating cohorts, 1993, 1996, 1999, 2000, and 2002 (i.e. in the years 2003, 2006, 2009, 2010 and 2012, respectively). We used multivariable binary logistic regression models to examine the influence of a number of personal and professional characteristics on the likelihood of working LTFT in male and female doctors. Results: Across all cohorts, 42% of women and 7% of men worked LTFT. For female doctors, having children significantly increased the likelihood of working LTFT, with greater effects observed for greater numbers of children and for female doctors in non-primary care specialties (non-GPs). While >40% of female GPs with children worked LTFT, only 10% of female surgeons with children did so. Conversely, the presence of children had no effect on male working patterns. Living with a partner increased the odds of LTFT working in women doctors, but decreased the odds of LTFT working in men (independently of children). Women without children were no more likely to work LTFT than were men (with or without children). For both women and men, the highest rates of LTFT working were observed among GPs (~10 and 6 times greater than non-GPs, respectively), and among those not in training or senior positions. Conclusions: Family circumstances (children and partner status) affect the working patterns of women and men differently, but both sexes respond similarly to the constraints of their clinical specialty and seniority. Thus, although women doctors comprise the bulk of LTFT workers, gender is just one of several determinants of doctors’ working patterns, and wanting to work LTFT is evidently not solely an issue for working mothers.